2000
DOI: 10.2165/00003495-200059050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Intermittent Claudication

Abstract: Intermittent claudication, a symptom of atherosclerosis in the large vessels of the lower limbs, greatly affects patient mobility and quality of life. Medical therapy for a moderate form of this condition includes vasodilators, antiplatelet agents and alternative treatments such as ginkgo biloba.A meta-analysis of results from 52 trials (including 5088 patients) was conducted for all current medical therapies for intermittent claudication. After 24 weeks, some of the medical therapies were found to be more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 59 publications
0
26
0
5
Order By: Relevance
“…No less than 13 systematic reviews dealt with ginkgo (Ginkgo biloba) extracts (see table 1). Seven of these reviewed trials (total number of trials covered in any of the reviews 15) in patients with intermittent claudication [7][8][9][10][11][12][13]. Most of these reviews concluded that ginkgo extracts were significantly more effective than placebo in increasing measures like walking distance but the clinical relevance of the effects was felt to be moderate by some reviewers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No less than 13 systematic reviews dealt with ginkgo (Ginkgo biloba) extracts (see table 1). Seven of these reviewed trials (total number of trials covered in any of the reviews 15) in patients with intermittent claudication [7][8][9][10][11][12][13]. Most of these reviews concluded that ginkgo extracts were significantly more effective than placebo in increasing measures like walking distance but the clinical relevance of the effects was felt to be moderate by some reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…For the compilation of this register a variety of databases including Medline, Embase, CIS-COM, AMED and other sources have been searched. In addition, we searched 1) Medline 1989 to July 2000 using a standard strategy to identify systematic reviews [8] combined with 50 single plant names and the 'exploded' term 'medicinal plants'; 2) the Cochrane Library (last check in issue 2000, 3) Bibliographies of articles obtained and relevant textbooks were screened for further potentially relevant articles. The literature list from the Complementary Medicine Field register was screened in a first step independently by two reviewers who excluded all references for which they were sure that the papers were not systematic reviews.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the 300 and 600 mg forms have been withdrawn from the market, the 150 mg dosage is kept with the only indication of IC 48 Given the limited evidence on efficacy and the narrow therapeutic range, the present benefit-risk ratio of buflomedil is considered as marginal. With pentoxifylline several RCTs have been performed and there are at least 4 reviews on its use in IC [49][50][51][52] . The trials were of varying quality.…”
Section: Drugs With Limited And/or Doubtful Evidencementioning
confidence: 99%
“…5,6 Despite numerous randomized, placebo-controlled trials, however, lack of protocol standardization and resulting inconsistencies in the demonstrated magnitude of therapeutic effect have created significant uncertainty as to the appropriate role of cilostazol. 7 In the United Kingdom and Europe, naftidrofuryl oxalate has been available since 1972. Several metaanalyses have suggested a statistically significant and clinically meaningful effect of naftidrofuryl compared with placebo and/or pentoxifylline.…”
Section: Introductionmentioning
confidence: 99%
“…Several metaanalyses have suggested a statistically significant and clinically meaningful effect of naftidrofuryl compared with placebo and/or pentoxifylline. [7][8][9] In the midst of uncertainties over the efficacy of these vasoactive drugs for IC, the National Institute for Health and Care Excellence (NICE) of the United Kingdom published a technology appraisal guidance in May 2011 based on systematic reviews, meta-analyses, and cost-effectiveness analyses. 10 This document concludes provocatively that naftidrofuryl oxalate is the only recommended option for the treatment of IC, whereas cilostazol is not recommended.…”
Section: Introductionmentioning
confidence: 99%